Medida das curvaturas do grão em metais - Augusto, Fabiana Pinto Miguel (2007)
The grain of any material is formed by a group of atoms which have the same orientation. A set of grains compose the metal structure. The material mechanical properties are directly related to its microstructure, being influenced by the grain size. The mean intercept length, l the grain boundary area per unit of volume, Sv; the mean grain boundary curvature, mean edge curvature, and the mean grain curvature, are metallographic measurements made in a planar section of the material which describes very well this microstructure. At this paper metallographic techniques to perform the described above measurements are applied on: Al-1wt%Mn, steel interstitial free, Niobium-low alloyed steel, electric steel of non-oriented grains and pure iron specimen in order to describe the influence of the grain curvature on grain growth. The resulting experimental data is compared with existing geometric models.